Analisis Kemampuan Pemecahan Masalah Matematika Siswa SMA pada Materi Lingkaran - Konda, Henny; Palayukan, Hersiyati; Ba’ru, Yusem (Jurnal Pendidikan Matematika : Judika Education, 2026)
This study aims to analyze the mathematical problem-solving skills of Class XI P3 students at SMA Negeri 5 Tana Toraja in solving contextual problems related to the topic of Circles, using the Problem-Based Learning model integrated with a deep learning approach. This research employed a qualitative method. The results indicated that 86% of the students demonstrated the ability to select appropriate formulas or strategies and accurately formulate mathematical models from the given problems. Meanwhile, 62% of the students successfully executed their problem-solving plans and achieved the correct results. In conclusion, the mathematical problem-solving skills of Class XI P3 students at SMA Negeri 5  Tana Toraja on the topic of Circles, utilizing a deep learning approach, are classified as good.   Keywords: Mathematical Problem-Solving Skills, Deep Learning, Problem-Based Learning.